The new era of space food system: a review - Patil, Shital; Swami, Uddhav; Shetty, Shruti; Phalke, Purva; Sahoo , A K (Journal of Postharvest Technology, 2022)
Space food is a kind of food item made and prepared for utilization by space explorers during missions to space. Food ought to be solid and nutritious as space travelers face numerous medical conditions because of the absence of legitimate air. Space explorers initially conveyed food in space on Mercury’s mission. After that, the food of various assortments was devoured on missions, for example, Gemini, Apollo, Skylab, Apollo Soyuz test project, and in the International space station. Different techniques like drying, irradiation, freeze-drying, and refrigeration are utilized for Physicochemical, Sensorial and Microbial security of room food. Freeze-drying methods in the space program comprise cutting, dicing, or condensing arranged food to decrease planning time. A space explorer can browse numerous kinds of food varieties like organic products, nuts, peanut butter, chicken, meat, fish, treats, brownies and so forth and beverages incorporate espresso, tea, squeezed orange, fruit juices and lemonade. As of late, space food has been utilized by different countries connecting with on space programs as an approach to share and flaunt their social personality and encourage intercultural correspondence.